Festival Anak Saleh di Desa Leang-leang Kabupaten Maros - Aswar Aswar; Rosmita Rosmita (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2020)
Community service (PkM) is one pillar of Tri Dharma in Higher Education. One form of its realization is cooperation between the regional government and universities in the form of implementing KKN that is sustainable and provides mutual benefit (symbiosis of mutualism). The purpose of this PkM was to improve the competence, morals, and attitude of elementary-school-age children in Leang-Leang village through the implementation of a program titled "Virtuous Children's Festival" (FAS) organized by the students of Community Service Program (KKN) III STIBA Makassar, which was directly guided by a Field Supervisor (DPL). As for the forms of competition in FAS those were: Adhan competition, Musabaqah Tilawatil Quran (MTQ), Musabaqah Hifdzil Quran (MHQ), Islamic Intelligence Quiz (CCI), and Little Da'i. Method of the implementation of the program was analyzing the needs of elementary-school-age children, planning, implementing, and evaluating and following up on activities. The results of PkM are that elementary-school-age children have had basic Islamic knowledge, memorized short letters of Quran and daily prayers, and are enthusiastic in learning Quran.